Assessment of executive functions and physical activity in girls and boys with normal weight, overweight and obesity. Issue 10 (31st May 2022) - Patraca‐Camacho, Lorena; Cibrián‐Llanderal, Tamara; Acosta‐Mesa, Héctor‐Gabriel; Rodríguez‐Landa, Juan Francisco; Romo‐González, Tania; Rosas‐Nexticapa, Marcela; Herrera‐Meza, Socorro
Summary: Objective: To evaluate the association between body mass index (BMI) and performance of executive functions (EFs) in girls and boys with 9‐ and 10‐year‐old schoolchildren with moderate‐ to vigorous‐intensity physical activity (MVPA) and sedentary behaviour. Methods: A total of 120 schoolchildren (61 girls and 59 boys) were evaluated anthropometrically. The MVPA was evaluated with a self‐report questionnaire. EFs were measured using a neuropsychological battery of Executive Functions and Frontal Lobes‐2 (BANFE‐2). Results: A high BMI was associated with longer delay in completing inhibitory control tests ( p  = 0.00, r p  = 0.32) and working memory ( p  = 0.00, r p  = 0.26). We observed correlations in time ( p  = 0.00, r p  = −0.43) and hits ( p  = 0.04, r p  = −0.27) of self‐directed signalling test in boys; and girls in alphabetical words order ( p  = 0.00, r p  = −0.39). Active normal weight schoolchildren (ANw) performed better by successfully completed the working memory tasks ( H  = 26.97, p  = 0.00) than sedentary schoolchildren with overweight and obesity. In addition, overweight‐active schoolchildren (AOw) showed better performance on working memory tests in time ( p  = 0.00) and hits ( p  = 0.01) than their sedentary peers. Multiple linear regression analysis revealed a significant association between BMI and EFs scores ( F  = 2.41, df  = 98, p  = 0.001). Conclusions: EFs are affected by a high BMI and sedentary behaviour in school children. Boys and girls reflected differences to solve the same challenges. The MVPA has a positive effect on executive control skills mainly in overweight children.